Bioinspired Helical Triboelectric Nanogenerators for Energy Conversion of Motion. Issue 4 (6th February 2020) - Li, Xiucheng; Mu, Jiliang; He, Jian; Fan, Xueming; Zhang, Qiyuan; Hou, Xiaojuan; Geng, Wenping; Zhang, Wendong; Chou, Xiujian
Abstract: Collecting energy from body movements to supply power for equipment is an important method to rapidly develop wearable intelligent equipment. This method places high requirements, such as being lightweight and stable, on a nanogenerator. Herein, a bioinspired helical triboelectric nanogenerator (BH‐TENG) that realizes energy acquisition through the intensity and frequency of body movement is designed based on the helical structure of DNA. The helical structure facilitates more contact areas and provides increased stability to complete the power generation process than the simple structure with planar electrodes and functional layers in the same volume. It is found that when the frequency is 4 Hz and the impact load is 50 N, the output current reaches 17 µA and the voltage reaches 300 V with a charge transfer capacity of 371 nC. When the BH‐TENG is fitted in the sole of a shoe, it can light 120 LEDs when a subject is walking. After simple rectification output and capacitance matching, the BH‐TENG is verified to work independently and stably for 20 min to provide power for small digital thermometer. The above experiments show the advantages of the BH‐TENG in acquiring body motion energy. Abstract : A bioinspired helical triboelectric nanogenerator (BH‐TENG) inspired by the double helix structure of DNA is reported as a motion energy harvester, which exhibits simple structure, small weight, high output, and high stability. The BH‐TENG realizes energy harvesting of human motion and drives electrical appliances such as wearable intelligent equipment through simple rectifier circuit.